The effect of internal migration on local labor markets American cities during the Great Depression - Boustan, Leah Platt; Fishback, Price 1955-; Kantor, Shawn Everett (Working paper series / National Bureau of Economic Research, 2007)
During the Great Depression, as in the modern era, in-migrants were accused of taking jobs and crowding relief rolls. Unlike today, the targets of protest during the Depression were typically American citizens from other parts of the country, rather than the foreign born. Using aggregate data on internal migration flows matched to individual records from the 1940 Census, we analyze the impact of internal migration on various labor market outcomes. To control for the likely endogeneity bias that would arise if migrants were attracted to areas with high wages or plentiful work opportunities, we instrument for migration flows. The instrument predicts out-migration from local areas using extreme weather events and variations in the generosity of New Deal programs and assigns these flows to destinations based on geographic distance. As in many contemporary studies of immigration, our results indicate that residents of metropolitan areas with high in-migration rates did not experience a drop in hourly earnings. Instead, longer term residents of high in-migration areas experienced three types of economic dislocation. A significant number moved away. Many of those who stayed experienced either a drop in annual weeks of work and/or reductions in access to work relief jobs. During a Depression with extraordinary unemployment and an extensive amount of job sharing, these lost work opportunities were costly to existing residents.